On a Special Form of (h) hν-Torsion Tensor Pijk in Finsler Space - Brijesh Kumar Tripathi; K. B. Pandey (Journal of Mathematics)
A special form of (h) hν-torsion tensor was introduced which may be considered generalization of P⁎-Finsler space and P-reducible Finsler space and then some properties of this space were studied. We also introduce connection and give some case and condition of torsion tensor Tjki.